Mapping Antecedents and Outcomes of Marginality and Social Exclusion among Small Landholders: A Systematic Review - Sikandar, Furqan; Wang , Hong Shu; Zahra, Kanwal; Muhammad Yaseen , Bilal; Ullah , Saif; Shobairi, Seyed Omid Reza (Ecological Questions, 2023)
This study aims to review determinants of the social exclusion (SE) of small farmers in the agriculture sector, which is one of the key approaches to creating sustainable rural development and an integral part of the country’s economic development. The selected group’s social and economic underpinnings play a vital role in their productive decision-making regarding rural development. As per the literature review, databases of peer-reviewed scientific publications, and official publications of the relevant fields from 2005 to 2020, it has been deduced that the literature lacks elucidated support on the small landholder (SLH) in defining their marginality and social exclusion. This study particularly attempts to fill this gap by reviewing the comprehensive research of said domains. A precise and effective list of main players in this field to the smallholders throughout the developing and developed countries has been produced. Findings indicate that government interventions in terms of the welfare system, credit facilities, agriculture resources, market access, and farmers’ migration significantly influence decreasing social exclusion, food security, and attainment of the SDGs. Moreover, educational systems through farmer social networks, farmer-based organizations, and farmer field schools help adapt to climate change and the latest agricultural technologies, increase livelihood choices, reduce poverty and inequalities, empower women, and improve the social status of farmers. This is ultimately and positively associated with the social inclusion of small farmers and sustainable economic development.